Evaluating water-induced wellbore instability in shale formations: a comparative analysis of transversely isotropic strength criteria - Yuqi Zhang; Xuejia Du; Dingwen Jiang (Frontiers in Earth Science)
This study addresses wellbore instability in shale formations by conducting mechanical experiments on bedded shale samples with varying hydration times. We fitted experimental data using two anisotropic strength criteria to determine the shale’s strength parameters. A transverse isotropic stress model was developed to predict the lower limit of the safe drilling fluid density window, examining the effects of hydration time and anisotropy on wellbore stability. Results indicate that rock strength initially increases and then decreases with bedding angle. Within the β1 to β2 range, both the Jaeger’s Plane of Weakness model (JPW) and Plane of Patchy Weakness Model (PPW) accurately predicted shale strength; however, below β1, the JPW criterion overestimated strength, while the PPW criterion better reflected strength variations. Anisotropy due to bedding significantly increased wellbore collapse pressure, shifting the optimal well trajectory from the direction of minimum horizontal stress to maximum horizontal stress, altering collapse pressure contour distributions. The choice of strength criteria had minimal impact on the trend of collapse pressure with well trajectory. While shale hydration can significantly affect wellbore stability and the lower safe drilling mud window with well trajectory, prolonged contact between drilling fluid and rock gradually increased lower safe drilling mud window. Collapse pressure in vertical or horizontal wellbores was minimally affected by soaking time, whereas inclined wellbores showed greater sensitivity. Notably, horizontal wells drilled in the direction of minimum horizontal stress were more responsive to contact time with drilling fluid, leading to a faster increase in collapse pressure.